Preparation method and application of amorphous metal oxide nanorod negative electrode material

By using amorphous metal oxide nanorod negative electrode material in lithium-ion batteries, the problems of limited specific capacity and poor cycle stability of traditional materials are solved, high specific capacity and good cycle stability are achieved, and the overall performance of the battery is improved.

CN119612597APending Publication Date: 2025-03-14NINGBO VEKEN BATTERY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411613647.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-05
Filing Date
2024-11-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The theoretical specific capacity of traditional graphite negative electrode materials is limited, which is difficult to support the demand of high-energy-density battery systems. In addition, metal oxide materials are prone to volume expansion during charging and discharging, affecting cycle stability, and the preparation process is complex and costly.

Method used

Amorphous metal oxide nanorod negative electrode material is used to regulate the interaction between metal ions and ligands through soft, hard and alkali coordination theory, and realize the synthesis of amorphous structures. The nanorod structure is used to improve the specific surface area and electronic conductivity, adapt to volume changes, and reduce mechanical stress.

Benefits of technology

It improves the specific capacity and cycle stability of lithium-ion batteries, enhances the fast charging and discharging capacity, reduces the risk of material failure, extends the cycle life of the battery, and improves the overall conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612597A_ABST
    Figure CN119612597A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of negative electrode materials, and relates to a preparation method and application of an amorphous metal oxide nanorod negative electrode material. The preparation method of the amorphous metal oxide nanorod negative electrode material comprises the following steps: uniformly mixing an organic ferric salt and an organic manganese salt, adding an organic ligand, stirring until precipitate appears, cleaning the precipitate, performing freeze drying, and then performing heat treatment to obtain the amorphous metal oxide nanorod negative electrode material. By adopting the nanorod structure, more reaction sites can be provided so as to promote the intercalation and deintercalation rates of lithium ions; due to the one-dimensional characteristic of the nanorod, the diffusion path of lithium ions in the material is shortened, and the rapid charging and discharging capacity is enhanced. In addition, the amorphous structure is adopted, so that the mechanical stress of the material can be reduced, and the cycling stability is improved; the electronic conductivity is superior to the performance of the same crystal state, and the overall conductivity of the battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials and relates to a preparation method and application of an amorphous metal oxide nanorod negative electrode material. Background Art

[0002] With the rapid development of renewable energy technology and the electric vehicle industry, the demand for high-performance battery materials has shown an unprecedented growth trend. In this context, although traditional graphite anode materials are known for their stable performance, they are difficult to support the requirements of the next generation of high-energy density battery systems due to the limitations of their theoretical specific capacity. Therefore, researchers have turned their attention to new materials with higher theoretical specific capacity, among which metal oxide nanomaterials have shown great potential as lithium-ion battery anode materials.

[0003] Metal oxides not only have high theoretical specific capacity, but their crystal structure can be optimized through doping or surface modification to further improve the performance of the material. x As a typical bimetallic oxide, it has attracted much attention due to its unique chemical composition. The combination of iron (Fe) and manganese (Mn) not only improves the theoretical specific capacity of the material, but also optimizes the diffusion path of lithium ions during the charge and discharge process, thereby improving the cycle stability and durability of the battery.

[0004] However, metal oxides also face some challenges. First, during the charge and discharge process, metal oxides are prone to significant volume expansion, which may lead to the destruction of the material structure and thus affect the cycle stability of the battery. Secondly, these materials themselves usually have low electronic conductivity and need to be compounded with conductive agents to enhance the efficiency of electron transfer. In addition, the preparation process of metal oxides is relatively complex and costly, which limits its promotion in large-scale applications.

[0005] In contrast, amorphous metal oxides can accelerate the diffusion rate of lithium ions due to their higher specific surface area, thereby enhancing the charge and discharge performance of the battery. The unique disorder of the amorphous structure allows the material to respond to volume changes more flexibly during the charge and discharge process, reduce internal mechanical stress, and further enhance cycle stability. In addition, compared with similar crystalline substances, amorphous materials perform better in electronic conductivity, which helps to improve the overall battery conductivity. However, the synthesis of amorphous materials cannot achieve the same controllability as crystals. This is because the synthesis and control of crystals rely on the inherent directionality of the lattice, which is undoubtedly not applicable to isotropic amorphous materials.

[0006] In summary, constructing a new and stable amorphous metal oxide structure shows broad application prospects in improving battery performance and extending service life, and is expected to become one of the key factors in promoting the advancement of battery technology in the future. Summary of the invention

[0007] In view of the above problems existing in the prior art, the present invention provides a method for preparing an amorphous metal oxide nanorod negative electrode material and its application.

[0008] One object of the present invention is achieved by the following technical solutions:

[0009] A method for preparing an amorphous metal oxide nanorod negative electrode material comprises the following steps: uniformly mixing an organic iron salt and an organic manganese salt, adding an organic ligand and stirring until precipitation occurs, washing the precipitation and freeze-drying it, and then performing heat treatment to obtain the amorphous metal oxide nanorod negative electrode material.

[0010] The present invention is based on the hard-soft acid-base coordination theory (HSAB theory), i.e., the basic principle of bonding behavior between acids (metal ions) and bases (ligands) with different polarization degrees. According to the HSAB theory, "hard acids" tend to combine with "hard bases", "soft acids" tend to combine with "soft bases", and the compounds formed by hard acids and soft bases or soft acids and hard bases are relatively unstable and have a low reaction rate. This rule can be summarized as "hard favors hard, soft favors soft". The synthesis of amorphous metal oxide nanorods is achieved by adjusting the interaction strength between metal ions and ligands.

[0011] Metal oxide nanorods, that is, nanoscale metal oxide rod-shaped structural materials, are a one-dimensional metal oxide nanostructure. Compared with conventional nanosheets or nanolayers, they have a higher specific surface area and can provide more reaction sites to promote the insertion and extraction rate of lithium ions, thereby improving battery performance. In addition, the unique one-dimensional characteristics of the nanorod structure greatly shorten the diffusion path of lithium ions in the material, enhancing the rapid charge and discharge capabilities. Its excellent electronic conductivity and good mechanical stability enable the nanorods to adapt to volume changes, reduce the risk of material failure, and extend the cycle life of the battery.

[0012] Preferably, the organic iron salt includes one or more of ferric acetylacetonate, ferric acetate and ferric oxalate.

[0013] Preferably, the organic manganese salt includes one or more of manganese acetylacetonate, manganese acetate and manganese oxalate.

[0014] Preferably, the organic ligand includes one or more of long-chain thiol ligands, organic amine ligands, phosphine ligands, carboxylic acid ligands, and multidentate ligands. The long-chain thiol ligands can be listed as dodecyl mercaptan, hexadecyl mercaptan, undecyl mercaptan, octadecyl mercaptan, tetradecyl mercaptan, etc.; the organic amine ligands can be listed as dodecylamine, ethylenediamine, hexadecylamine, octadecylamine, tetradecylamine, etc.; the phosphine ligands can be listed as triphenylphosphine, tributylphosphine, tricyclohexylphosphine, triphenylphosphine chloride, diphenylphosphine, methyldiphenylphosphine, etc.; the carboxylic acid ligands can be listed as stearic acid, oleic acid, palmitic acid, myristic acid, linoleic acid, etc.; the multidentate ligands can be listed as ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, tris(2-aminoethyl)amine, 2,2'-bipyridine, tris(2-pyridylmethyl)amine, etc.

[0015] More preferably, the organic ligand includes one or more of dodecyl mercaptan, hexadecyl mercaptan, and dodecylamine.

[0016] Preferably, the ratio of the organic iron salt, the organic manganese salt and the organic ligand is (0.1-3) g: (0.1-3) g: (1-50) mL.

[0017] Preferably, the step of mixing the organic iron salt and the organic manganese salt comprises: dissolving the organic iron salt and the organic manganese salt in solvents respectively, adding the organic manganese salt solution into the organic iron salt solution, and then stirring at 70 to 90° C. for 10 to 60 minutes to fully mix the organic iron salt and the organic manganese salt.

[0018] In the mixing step, preferably, the concentration of the organic iron salt in the solution is 0.001 to 0.01 g / mL, and the concentration of the organic manganese salt in the solution is 0.001 to 0.01 g / mL.

[0019] In the mixing step, preferably, the solvent includes one or more of toluene, dimethylformamide (DMF), dimethyl sulfoxide (DMSO), dimethylacetamide (DMAc), ethyl acetate, acetone, methyl ethyl ketone, ethanol, methanol, xylene, and tetrahydrofuran.

[0020] Preferably, after adding the organic ligand, the solution is stirred at 100-150° C. for 1-10 hours until precipitation occurs, and the precipitate is obtained by centrifugation.

[0021] Preferably, the precipitate is washed at least twice with cyclohexane and / or ethanol.

[0022] Preferably, the freeze-drying temperature is -40 to -10°C, and the time is 10 to 30 hours.

[0023] Preferably, the heat treatment comprises heating the temperature to 80-120° C. at a rate of 1-10° C. / min and keeping the temperature for 1-5 hours.

[0024] The second object of the present invention is achieved by the following technical solutions:

[0025] An amorphous metal oxide nanorod negative electrode material is prepared by the above preparation method.

[0026] Preferably, the general formula of the amorphous metal oxide nanorod negative electrode material is FeMnO x , where 2≤x≤3.

[0027] The third object of the present invention is achieved by the following technical solutions:

[0028] A negative electrode plate for a lithium-ion battery comprises the above-mentioned amorphous metal oxide nanorod negative electrode material.

[0029] Preferably, the negative electrode plate comprises an amorphous metal oxide nanorod negative electrode material, a conductive agent, and an auxiliary agent.

[0030] Preferably, the method for preparing the negative electrode sheet of a lithium-ion battery comprises the following steps: ball-milling and mixing the amorphous metal oxide nanorod negative electrode material, the conductive agent and the auxiliary agent, adding a solvent to form a negative electrode slurry, and then coating, vacuum drying and rolling to obtain the negative electrode sheet of a lithium-ion battery.

[0031] Preferably, the mass ratio of the amorphous metal oxide nanorod negative electrode material, the conductive agent, the auxiliary agent and the solvent is (90-100):(0.1-5.0):(0.1-5.0):(20-50).

[0032] Preferably, the conductive agent includes one or more of conductive carbon black Super P, Super S, graphene, carbon nanotubes, and carbon fibers.

[0033] Preferably, the auxiliary agent includes a binder and / or a thickener; the binder can be listed as one or more of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), etc.; the thickener can be listed as one or more of carboxymethyl cellulose (CMC), hydroxypropyl methyl cellulose (HPMC), etc.

[0034] Preferably, the solvent includes one or more of water, N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, isopropanol, and acetone.

[0035] The fourth object of the present invention is achieved by the following technical solutions:

[0036] A lithium-ion battery comprises the above-mentioned lithium-ion battery negative electrode plate.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. The present invention provides an amorphous metal oxide nanorod negative electrode material, which adopts a nanorod structure and has a higher specific surface area than conventional nanosheets or nanolayers. It can provide more reaction sites to promote the insertion and deinsertion rate of lithium ions and improve battery performance. In addition, the nanorod structure has a unique one-dimensional characteristic, which greatly shortens the diffusion path of lithium ions inside the material and enhances the rapid charging and discharging capability. Its excellent electronic conductivity and good mechanical stability enable the nanorods to adapt to volume changes, reduce the risk of material failure, and extend the cycle life of the battery.

[0039] 2. In the preparation method of an amorphous metal oxide nanorod negative electrode material provided by the present invention, the preparation is carried out by a liquid phase synthesis method based on the soft and hard acid-base coordination theory, and the reaction conditions are strictly controlled. It is suitable for preparing different types of metal oxides, and the synthesis of amorphous structure is achieved by adjusting the interaction strength between metal ions and ligands.

[0040] 3. The present invention adopts amorphous FeMnO x As negative electrode materials for lithium-ion batteries, metal oxide nanorods have high capacity and good cycle stability. Their amorphous structure provides more lithium ion embedding sites, improves specific capacity, effectively alleviates volume expansion, and prolongs cycle life. At the same time, the excellent conductivity of amorphous materials makes the migration of lithium ions more efficient and improves the charge and discharge rate.

[0041] 4. The amorphous metal oxide nanorod negative electrode material provided by the present invention has a high specific surface area, which helps to increase the diffusion rate of lithium ions, thereby improving the charge and discharge performance of lithium-ion batteries. Secondly, the disorder of the amorphous structure enables the material to better adapt to volume changes during the charge and discharge process, reduce the mechanical stress of the material, and improve the cycle stability. In addition, the amorphous material shows better performance than its crystalline counterpart in terms of electronic conductivity, which can effectively improve the overall conductivity of the battery. Therefore, the amorphous metal oxide structure FeMnO x It has important application prospects in improving battery performance and extending service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the TEM spectrum of the amorphous metal oxide nanorod negative electrode material of Example 1 of the present invention.

[0043] Figure 2 This is the XRD spectrum of the amorphous metal oxide nanorod negative electrode material of Example 1 of the present invention.

[0044] Figure 3This is a comparison chart of the discharge specific capacity of lithium-ion batteries prepared with the amorphous metal oxide nanorod negative electrode material of Example 1 of the present invention and the crystalline metal oxide nanorod negative electrode material of Comparative Example 1 at different rates.

[0045] Figure 4 This is a comparison chart of the cycle performance of lithium-ion batteries prepared with the amorphous metal oxide nanorod negative electrode material of Example 1 of the present invention and the crystalline metal oxide nanorod negative electrode material of Comparative Example 1. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0047] Example 1

[0048] The preparation method of the amorphous metal oxide nanorod negative electrode material in this embodiment comprises the following steps:

[0049] (1) Place 0.5 g of ferric acetylacetonate in a flask, add 75 ml of toluene to dissolve it, and then ultrasonicate it to make it evenly dispersed;

[0050] (2) After the solution obtained in step (1) is evenly dispersed, 0.5 g of manganese acetylacetonate and 75 ml of toluene are added and evenly dispersed by ultrasonication, and then placed in an oil bath at 80° C. and stirred for 30 min to fully mix the iron acetylacetonate and manganese acetylacetonate;

[0051] (3) adding 10 ml of dodecyl mercaptan to the solution obtained in step (2), and stirring the solution at 120° C. for 5 h until precipitation occurs;

[0052] (4) The solution obtained in step (3) was centrifuged to obtain a precipitate, which was washed with cyclohexane and ethanol three times, and freeze-dried at -20°C for 12 hours; then placed in a tube furnace, heated to 100°C at a rate of 5°C / min and kept warm for 2 hours to obtain amorphous FeMnO 3 Metal oxide nanorods anode materials.

[0053] Figure 1 This is the TEM spectrum of the amorphous metal oxide nanorod negative electrode material of Example 1 of the present invention; Figure 2 This is the XRD spectrum of the amorphous metal oxide nanorod negative electrode material of Example 1 of the present invention.

[0054] from Figures 1-2It can be seen that amorphous FeMnO 3 The metal oxide nanorod negative electrode material of the present invention innovatively combines the soft and hard acid-base coordination theory with liquid phase synthesis, accurately controls the reaction conditions, and realizes the synthesis of amorphous structure by adjusting the interaction strength between metal ions and ligands, ensuring that the element ratio and morphology of the amorphous metal oxide nanorod negative electrode material are more uniform.

[0055] Example 2

[0056] The preparation method of the amorphous metal oxide nanorod negative electrode material in this embodiment comprises the following steps:

[0057] (1) Place 0.3 g of ferric acetylacetonate in a flask, add 50 ml of toluene to dissolve it, and then ultrasonicate it to make it evenly dispersed;

[0058] (2) After the solution obtained in step (1) is evenly dispersed, 0.7 g of manganese acetylacetonate and 100 ml of toluene are added and evenly dispersed by ultrasonication, and then placed in an oil bath at 80° C. and stirred for 30 min to fully mix the iron acetylacetonate and manganese acetylacetonate;

[0059] (3) adding 15 ml of hexadecyl mercaptan to the solution obtained in step (2), and stirring the solution at 120° C. for 5 h until precipitation occurs;

[0060] (4) The solution obtained in step (3) was centrifuged to obtain a precipitate, which was washed with cyclohexane and ethanol three times, and freeze-dried at -20°C for 12 hours; then placed in a tube furnace, heated to 100°C at a rate of 5°C / min and kept warm for 2 hours to obtain amorphous FeMnO 3 Metal oxide nanorods anode materials.

[0061] Example 3

[0062] The preparation method of the amorphous metal oxide nanorod negative electrode material in this embodiment comprises the following steps:

[0063] (1) Place 0.7 g of ferric acetylacetonate in a flask, add 100 ml of toluene to dissolve it, and then perform ultrasonication to make it evenly dispersed;

[0064] (2) After the solution obtained in step (1) is evenly dispersed, 0.3 g of manganese acetylacetonate and 50 ml of toluene are added and evenly dispersed by ultrasonication, and then placed in an oil bath at 80° C. and stirred for 30 min to fully mix the iron acetylacetonate and manganese acetylacetonate;

[0065] (3) adding 20 ml of dodecylamine to the solution obtained in step (2), and stirring the solution at 120° C. for 5 h until precipitation occurs;

[0066] (4) The solution obtained in step (3) was centrifuged to obtain a precipitate, which was washed with cyclohexane and ethanol three times, and freeze-dried at -20°C for 12 hours; then placed in a tube furnace, heated to 100°C at a rate of 5°C / min and kept warm for 2 hours to obtain amorphous FeMnO 3 Metal oxide nanorods anode materials.

[0067] Comparative Example 1

[0068] The preparation method of the crystalline metal oxide nanorod negative electrode material of this comparative example comprises the following steps:

[0069] Amorphous FeMnO was prepared according to the preparation method of Example 1. 3 Metal oxide nanorods as negative electrode materials, then in Ar / H 2 The product was annealed at 350 °C for 2 h in a (90% / 10%) atmosphere, and then washed with deionized water and ethanol for three times and dried to obtain crystalline FeMnO 3 Metal oxide nanorods anode materials.

[0070] The negative electrode materials of the embodiment and the comparative example are used to prepare a lithium ion battery, comprising the following steps: weighing the negative electrode materials, conductive carbon black SP, binder SBR, thickener CMC and solvent water prepared in the embodiment and the comparative example at a mass ratio of 100:5:2.5:2.5:50; uniformly mixing the negative electrode materials, conductive carbon black SP, binder SBR, thickener CMC and solvent water, maintaining high-speed stirring for 5 hours, with a revolution speed of 400 m / s and a dispersion speed of 30 m / s to form a negative electrode slurry; then coating the mixture on an aluminum foil, and obtaining a negative electrode sheet after vacuum drying at 100° C. and rolling; then mixing the negative electrode sheet, the counter electrode sheet, and the electrolyte (the solute is LiPF 6 , concentration is 1 mol / L, solvent is EC:DEC=1:1) and glass fiber separator are assembled to obtain a lithium ion battery, and relevant battery performance tests are carried out. The specific test method is as follows.

[0071] 1. Discharge capacity test at different rates

[0072] First, the battery was placed in an environment of 25±2℃ for 8h, then charged to 4.8V at a constant current of 0.5C, followed by standing for 5min, then charged at a constant voltage of 4.8V to a current of 0.05C, stood for 5min, and then discharged at a constant current of 0.1C / 0.2C / 0.5C / 1.0C to a voltage of 2.8V. The resulting capacity was recorded as the 0.1C / 0.2C / 0.5C / 1.0C discharge capacity.

[0073] 2. Cycle performance test

[0074] First, place the battery in a 25±2℃ environment for 8h, then charge it to 4.8V at a constant current of 0.5C, then let it stand for 5min, then charge it at a constant voltage of 4.8V to a current of 0.05C, let it stand for 5min, then discharge it to 2.8V at a constant current of 0.5C, repeat the above cycle for 150 times, and finally stop the operation, record the discharge capacity from the 1st to the 150th cycle, and calculate the capacity retention rate as follows:

[0075] The n-th cycle capacity retention rate = the n-th cycle discharge capacity / the 1st cycle discharge capacity (1≤n≤300).

[0076] For detailed test results, see Figures 3-4 and Table 1.

[0077] Figure 3 The following is a comparison chart of the discharge specific capacity of lithium ion batteries prepared from the amorphous metal oxide nanorod negative electrode material of Example 1 of the present invention and the crystalline metal oxide nanorod negative electrode material of Comparative Example 1 at different rates. Among them, at 0.1C, the discharge specific capacity of the amorphous metal oxide nanorod negative electrode material is 1150mAh / g, and the discharge specific capacity of the crystalline metal oxide nanorod negative electrode material is 1000mAh / g; at 0.2C, the discharge specific capacity of the amorphous metal oxide nanorod negative electrode material is 1010mAh / g, and the discharge specific capacity of the crystalline metal oxide nanorod negative electrode material is 960mAh / g; at 0.5C, the discharge specific capacity of the amorphous metal oxide nanorod negative electrode material is 990mAh / g, and the discharge specific capacity of the crystalline metal oxide nanorod negative electrode material is 890mAh / g; at 1.0C, the discharge specific capacity of the amorphous metal oxide nanorod negative electrode material is 920mAh / g, and the discharge specific capacity of the crystalline metal oxide nanorod negative electrode material is 820mAh / g.

[0078] Figure 4 The cycle performance comparison diagram of the lithium ion battery prepared by the amorphous metal oxide nanorod negative electrode material of Example 1 of the present invention and the crystalline metal oxide nanorod negative electrode material of Comparative Example 1. Among them, the capacity retention rate of the amorphous metal oxide nanorod negative electrode material is 96% at 50 cycles, 94% at 100 cycles, 92% at 150 cycles, 91% at 200 cycles, 87% at 250 cycles, and 83% at 300 cycles; the capacity retention rate of the crystalline metal oxide nanorod negative electrode material is 93% at 50 cycles, 88% at 100 cycles, 82% at 150 cycles, 77% at 200 cycles, 73% at 250 cycles, and 68% at 300 cycles.

[0079] Table 1 is a table showing the discharge specific capacity and 300 cycle performance data of lithium-ion batteries prepared with metal oxide nanorod negative electrode materials in the examples and comparative examples at a rate of 1.0C.

[0080] Table 1 Performance test data of embodiments and comparative examples

[0081] 1.0C discharge capacity mAh / g 300 cycles capacity retention rate % Example 1 920 83 Example 2 910 80 Example 3 915 79 Comparative Example 1 820 68

[0082] from Figures 3-4 As can be seen from Table 1, the amorphous metal oxide nanorod negative electrode material synthesized by the technical solution of the present invention has high specific capacity and good cycle stability. Compared with similar crystalline materials, its amorphous structure provides more lithium ion embedding sites, improves the specific capacity, and effectively alleviates volume expansion, thereby extending the cycle life. At the same time, the excellent electrical conductivity of the amorphous material makes the migration of lithium ions more efficient, thereby improving the charge and discharge rate.

[0083] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0084] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0085] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A method for preparing an amorphous metal oxide nanorod negative electrode material, characterized in that: The preparation method comprises the following steps: uniformly mixing an organic iron salt and an organic manganese salt, adding an organic ligand and stirring until precipitation occurs, washing the precipitation and freeze-drying it, and then performing heat treatment to obtain an amorphous metal oxide nanorod negative electrode material.

2. The preparation method according to claim 1, characterized in that: The organic iron salt includes one or more of ferric acetylacetonate, ferric acetate, and ferric oxalate; And / or, the organic manganese salt includes one or more of manganese acetylacetonate, manganese acetate, and manganese oxalate; And / or, the organic ligand includes one or more of long-chain thiol ligands, organic amine ligands, phosphine ligands, carboxylic acid ligands, and multidentate ligands.

3. The preparation method according to claim 1, characterized in that: The ratio of the organic iron salt, the organic manganese salt and the organic ligand is (0.1-3) g: (0.1-3) g: (1-50) mL.

4. The preparation method according to claim 1, characterized in that: The mixing step of the organic iron salt and the organic manganese salt comprises: dissolving the organic iron salt and the organic manganese salt in solvents respectively, adding the organic manganese salt solution into the organic iron salt solution, and then stirring at 70-90° C. for 10-60 minutes to fully mix the organic iron salt and the organic manganese salt.

5. The preparation method according to claim 4, characterized in that: The concentration of the organic iron salt in the solution is 0.001-0.01 g / mL, and the concentration of the organic manganese salt in the solution is 0.001-0.01 g / mL.

6. The preparation method according to claim 1, characterized in that: After adding the organic ligand, the solution is stirred at 100-150° C. for 1-10 hours until a precipitate appears, and the precipitate is obtained after centrifugation; the precipitate is washed at least twice with cyclohexane and / or ethanol; And / or, the heat treatment comprises heating to 80-120° C. at a rate of 1-10° C. / min and keeping the temperature for 1-5 hours.

7. An amorphous metal oxide nanorod negative electrode material, characterized in that: The invention discloses a method for preparing the present invention according to any one of claims 1 to 6.

8. The amorphous metal oxide nanorod negative electrode material according to claim 7, characterized in that: The general formula of the amorphous metal oxide nanorod negative electrode material is FeMnO x , where 2≤x≤3.

9. A negative electrode plate for a lithium ion battery, characterized in that: The negative electrode plate of the lithium-ion battery comprises an amorphous metal oxide nanorod negative electrode material as described in claim 7.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a lithium-ion battery negative electrode plate as claimed in claim 9.